Post-mortem evidence of idiopathic left ventricular hypertrophy and idiopathic interstitial myocardial fibrosis: is exercise the cause?. Issue 4 (24th August 2007) - Whyte, G; Sheppard, M; George, K; Shave, R; Wilson, M; Prasad, S; O'Hanlon, R; Sharma, S
Abstract : A growing body of evidence reporting altered cardiac function and myocardial damage after arduous exercise, together with the increased prevalence of arrhythmias observed in highly trained athletes, suggests that repetitive bouts of prolonged, arduous exercise may be deleterious to long-term cardiac health. We report the case of an experienced, highly trained marathon runner who died suddenly while running. On post-mortem examination, left ventricle hypertrophy and idiopathic interstitial myocardial fibrosis was found. We believe that life-long, repetitive bouts of arduous physical activity resulted in fibrous replacement of the myocardium, causing a pathological substrate for the propagation of fatal arrhythmias.